CERVICAL TOTAL DISC REPLACEMENT: Cervical Total Disc Replacement - Qureshi, Col Muhammad Asad; Afzal, Waseem; Malik, Arslan S; Khalique, Ahmed Bilal; Aebi, Max (Pakistan Armed Forces Medical Journal, 2010)
Traditional gold standard operation of anterior cervical discectomy and fusion (ACDF) has been challenged in the recent past. Cervical total disc replacement (TDR) has been suggested as an alternative to preserve motion and prevent complications associated with ACDF. Many recent randomly controlled trials (RCTs) have proven TDR equivalent to, if not superior to ACDF with added advantages of preserving motion and decreasing donor site morbidity1. In this article we present two cases that have completed at least one year follow up. To our knowledge this is the first case report of cervical TDR from Pakistan